Educação e linguagem : contribuições da enunciação oral do professor ao desenvolvimento da habilidade de investigar na formação de psicólogos - Slomp, Caroline (My University, 2014)
This research aims to analyze the professor’s language related to the p upil’s process of learning in the aspect of how the professor’s discourse influences the development of the ability of investigation done by the Psychology Course scholars. This research tried to answer the following question: How can the professor, using his/her speech, problematize the classroom content in order to contribute to the undergraduate students of Psychology to develop their ability to investigate? In an attempt to respond to this concern, it was established some issues which guided the research process: (1) How can the ability of investigation be developed by the students in their process of learning during their graduation course?; (2) What are the language features, present in the speech, which may contribute to the development of the ability of investigation of the undergraduation students of Psychology?; and (3) How can the problematization done through the professor’s speech contribute to the development of the ability of investigation of the undergraduation students? The present study aimed to answer these questions with bibliographical research, including observations from my own practice as a professor in the undergraduate course of Psychology. The study with theoretical characteristics discusses the development of the ability of investigation as a learning process in which occurs the mobilization of cognitive resources, mental operations, in order to solve problems. This study also suggests alternatives to the understanding the aspects of language present in the psychologist’s investigative process and in the interaction between the professor and his/her students based on Benveniste’s Theory of Enunciation. There are some other alternative proposals of response to guiding questions of this research, in order to assist the education of the Psychology students to point out some possibilities for professor to use features present in their oral language, to discuss the teaching, so as to contribute to the development of the ability of investigation. The study also stresses the importance of knowing how to ask to both the psychologist and the professor who seek to collaborate with the development of the investigation.
Esta investigação teve como objetivo analisar a relação da linguagem docente com a aprendizagem de alunos, no que se refere a influências do discurso docente no desenvolvimento da habilidade de investigar por acadêmicos do curso de Psicologia. O problema de pesquisa questiona: Como o professor, através de seu discurso, pode problematizar o conteúdo em sala de aula, de forma a contribuir para que o aluno do curso de graduação em Psicologia desenvolva a habilidade de investigar? Na tentativa de responder a essa inquietação, foram estabelecidas questões que nortearam o processo de investigação: (1) Como a habilidade de investigar pode ser desenvolvida pelo aluno em seus processos de aprendizagem durante a graduação em Psicologia?; (2) Quais são os recursos de linguagem, presentes no discurso docente, passíveis de contribuir para o desenvolvimento da habilidade de investigar dos alunos do curso de graduação em Psicologia?; e (3) Como a problematização, pelo discurso docente, pode contribuir para o desenvolvimento da habilidade de investigar dos alunos do curso de graduação em Psicologia? O presente estudo buscou responder a essas questões propostas por meio de pesquisa bibliográfica, incluindo observações decorrentes de minha prática como docente em curso de graduação em Psicologia, relacionadas à proposta desta investigação. O estudo, de caráter teórico, aborda o desenvolvimento da habilidade de investigar como um processo da aprendizagem em que ocorre a mobilização de recursos cognitivos, operações mentais, para resolver situaçõesproblema. Também sugere alternativas para a compreensão de aspectos da linguagem presentes no investigar do psicólogo e na interação professor/aluno, com base na teoria enunciativa de Benveniste. São ainda propostas alternativas de resposta às questões norteadoras da pesquisa, no sentido de auxiliar a formação de estudantes de Psicologia ao apontar possibilidades de os professores utilizarem recursos presentes em sua linguagem oral, a fim de problematizar o ensino, de modo a colaborar com o desenvolvimento da habilidade de investigar do psicólogo. O estudo salienta, igualmente, a importância do saber perguntar tanto para o psicólogo, quanto para o professor que buscam colaborar com o desenvolvimento do investigar de seus alunos.
Keywords: Psicologia educacional; Linguagem e educação; Psicólogos; Formação profissional; Educação; Education and Language; Psychologist’s Educations; Professor’s Oral Enunciation